Factors Affecting and Affected Nurse's Job Satisfaction Before and During Covid-19: A Systematic Literature Review - Oktavia Setyaningrum, Martha; Nursalam, Nursalam; Fityasari P.K, Rizki; Farhanidiah, Silvia; Jermia, Gabriella Ester (Fundamental and Management Nursing Journal, 2022)
Introduction: : The global pandemic COVID-19 has affected health services including nursing. During the pandemic COVID-19, the high need on nursing services resulted imbalances between demands and supply of nurses, and less of job satisfaction. This study was aimed to systematically identify factors associated with nurse's job satisfaction before and during the pandemic COVID-19. Method: This study was reviewing published papers that met the inclusion criterias. Included studied were assessed for its quality using the Joanna Briggs Institute's critical appraisal checklists. Four electronic databases; ScienceDirect, Scopus, SAGE and PubMed were accessed comprehensively to retrieved targeted articles published from 2017 to 2020. A PRISMA 2020 flow diagram was applied to report the stages of search strategies. Results: A total 26 studies were selected in this review. Factors affecting nurse's job satisfaction before and during the pandemic COVID-19 can be classified as personal factors, organizational factors, and psychological factors. Psychosocial risk, emotional intelligence, workload, supervisor quality, and salary were found to have strong association with job satisfaction. Thus, turnover and burnout were the most frequent reasons reported by nurses before the pandemic COVID-19. Conclusion: Nurse's job dissatisfaction resulted turnover and burnout. The current study underlined three factors affecting nurse's job satisfaction as follow: personal, organizational and psychological factors. Therefore, it's imperative to increase job satisfaction by way controlling the aforementioned factors.